Development of a New Composite Energy-Absorber System for Aircraft and Helicopter Sub-Floors - Talebi Taher, Siavash (2005)
Considerable research interest has been directed towards the use of composite for crashworthiness applications, because they can be designed to provide impact energy absorption capabilities which are superior to those of metals when compared on weight basis. The use of composite parts in structural and semi-structure applications is becoming more widespread throughout the automotives, aircraft and space vehicles. In this study, an innovative lightweight composite energy-absorbing keel beam system has been developed to be retrofitted in aircraft and helicopter in order to improve their crashworthiness performance. The developed system consists of everting stringer and keel beam. The sub floor seat rails were designed as everting stringer to guide and control the failure mechanisms at pre-crush and post crush failure stages of composite keel beam webs and core. Polyurethane foam was employed to fill the core of the beam to eliminate any hypothesis of global buckling. The numerical prediction was obtained using commercially available finite element analysis software. The experimental data are correlated with predictions from finite element model and analytical solution. An acceptable agreement between the experimental and computational results was obtained. For all structures considered classical axial collapse eigen values were computed. The results showed that the crushing behaviour of the developed system is found to be sensitive to the change in keel beam core cross-section. Laminate sequence has a significant influence on the failure mode types, average crush loads and energy absorption capability of composite keel beam. The desired energy absorbing mechanism revealed that the innovated system can be used for aircraft and helicopter and meet the requirements, together with substantial weight saving.